For Adults Only: Queer Theory Meets the Self and Identity in Adult Education - A. Brooks; K. Edwards (Adult Education Research Conference, 1999)
This article brings the perspective of "Queer theory" to the field of Adult Education as a way of examining critically the notions of self, identity, and sexuality as they have been taken for granted within the field. Adult Education, like most fields of practice and research, assumes the Western ideals of the monadic self, clear and undisputed identities, and heterosexuality. However, the intersection of a strong postmodern voice in both academia and the popular culture, the increasing exploration of other-than-hetero-sexualities in the media, and the foregrounding of sexuality in the work of adult education researchers (Brooks & Edwards,1997; Edwards, 1997; Hill,1995; Edwards, Grace, Henson, B., Henson, W., Hill, & Taylor, 1998; Tisdell & Taylor, 1995) forces the question of what relevance Queer theory has for adult educators.